"A Day On, Not a Day Off": Transforming Martin Luther King Day (1993–1999). (24th December 2020) - FLEMING, DANIEL T.
Abstract : Inspired by Martin Luther King's "Drum Major Instinct" sermon, President Bill Clinton signed the King Holiday and Service Act of 1994 and transformed the King holiday into a day of service. By linking the holiday to his community service initiatives, Clinton, and Coretta Scott King, encouraged Americans to continue King's work by helping America's poor through racially integrated service activities. Since the inaugural 1986 holiday, scholars have claimed that King Day abets amnesia more than it encourages remembrance; however, this reform illustrates that the holiday is an evolving and dynamic form of history that can be used to continue the work of the civil rights movement.